Overexpression of the sucrose transporter gene NtSUT1 alleviates aluminum-induced inhibition of root elongation in tobacco (Nicotiana tabacum L.). Issue 1 (2nd January 2017) - Kariya, Koki; Sameeullah, Muhammad; Sasaki, Takayuki; Yamamoto, Yoko
ABSTRACT: We aimed to investigate the role of the plasma membrane-localized sucrose/H + symporter gene ( NtSUT1 ) in root elongation growth of tobacco seedlings ( Nicotiana tabacum L. cv. Samsun NN) under aluminum (Al) stress, by comparative study between wild-type (WT) tobacco and constructed over-expression (OX) and suppression (RNAi) lines of NtSUT1, in which the overexpression or suppression of NtSUT1 was controlled by the cauliflower mosaic virus 35S promoter. Seedlings of each line were grown in a nutrient medium (pH 4.5) without or with aluminum chloride (AlCl3 ). The roots were analyzed to determine the degree of root elongation and the transcript levels of NtSUT1, soluble sugar content, and cell survival at the root apex. The transcript level of NtSUT1 at the root apex was negatively affected by Al. Compared with WT, OX lines and RNAi lines had higher and lower contents of soluble sugars at the root apex, respectively. Under a 16-h light/8-h dark photoperiod and in the absence of Al, the root elongation rate was similar in OX and WT, but was significantly decreased in RNAi. In the presence of Al, the degree of Al-induced inhibition of root elongation was lower in OX and higher in RNAi than in WT. At the root apex, the initiation of cell death during a 24-h Al treatment was decelerated in OX and accelerated in RNAi, compared with that in WT. The number of live cells remaining at the root apex after the 24-h Al treatment was higher in OX and lower in RNAi than in WT. In the dark, root growth was supported by sucrose supplied in the medium as a substitute for photoassimilate. Under these conditions in the absence or presence of Al, there were strong positive correlations between the transcript level of NtSUT1, the soluble sugar content at the root apex and the root elongation rate. Together, these results indicate that NtSUT1 at the root apex primarily supports sucrose uptake via the apoplastic pathway, and that sucrose positively affects root elongation. We conclude that overexpression of NtSUT1 at the root apex increases the soluble sugar content, resulting in greater cell survival and root elongation under Al stress, leading to the Al-tolerance phenotype.